2020
DOI: 10.3892/or.2020.7485
|View full text |Cite
|
Sign up to set email alerts
|

Periostin induces epithelial‑to‑mesenchymal transition via the integrin α5β1/TWIST‑2 axis in cholangiocarcinoma

Abstract: Periostin (PN) (also known as osteoblast-specific factor OSF-2) is a protein that in humans is encoded by the POSTN gene and has been correlated with a reduced survival of cholangiocarcinoma (CCA) patients, with the well-known effect of inducing epithelial-to-mesenchymal transition (EMT). The present study investigated the effect of PN, through integrin (ITG)α5β1, in EMT-mediated CCA aggressiveness. The alterations in EMT-related gene and protein expression were investigated by real-time PCR, western blot anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Twist2 has been demonstrated to be an important regulator and a poor diagnosis marker in some cancers [41][42][43][44], such as gastric cancer [42], cholangiocarcinoma [41], glioma [43], etc. Importantly, it has been revealed that it could accelerate cell proliferation, metastasis, and epithelialmesenchymal transition (EMT) in HCC [30,31,45].…”
Section: Discussionmentioning
confidence: 99%
“…Twist2 has been demonstrated to be an important regulator and a poor diagnosis marker in some cancers [41][42][43][44], such as gastric cancer [42], cholangiocarcinoma [41], glioma [43], etc. Importantly, it has been revealed that it could accelerate cell proliferation, metastasis, and epithelialmesenchymal transition (EMT) in HCC [30,31,45].…”
Section: Discussionmentioning
confidence: 99%
“…POSTN encodes for periostin, a multifunctional ECM protein that contributes to the remodeling of the tumor microenvironment during tumor progression [36]. In CCA and hepatoblastoma, overexpressed periostin was found to induce cell migration and epithelial-to-mesenchymal transition (EMT) features [37,38]. On the other hand, PUC-GBC1 cells exhibited a slower growth rate and an enhanced in vivo tumorigenic capability.…”
Section: Discussionmentioning
confidence: 99%
“…Periostin (POSTN), a matricellular N-glycoprotein, is implicated in the EMT process, and is crucial for the collagen fibrillogenesis process [ 184 , 185 ] and wound healing [ 186 , 187 ]. Cellular survival, motility, and adhesion are facilitated by POSTN-activated signalling pathways, which are essential for tumour growth, angiogenesis, invasion, and metastasis [ 188 , 189 , 190 ].…”
Section: Cafs Biomarkers: a Mixed Bagmentioning
confidence: 99%